Integrasi Literasi Keuangan dalam Pendidikan Menengah: Studi Kasus pada Siswa SMA Pangudi Luhur Kelas X: The Integration of Financial Literacy into Secondary Education: A Case Study of Grade 10 Students at Pangudi Luhur Senior High School, Jakarta - Tarigan, Thia Margaretha; Prasetyo, Christianus Yudi; Setiabudi, Andang Wirawan; Joseph, Katherine Olivia (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
This community service activity aims to integrate financial literacy into the secondary education curriculum to foster wise, responsible financial behavior. The program was implemented for Grade 10 students at SMA Pangudi Luhur Jakarta, focusing on three main aspects: personal financial management, investment understanding, and awareness of online loan risks. The implementation methods included interactive lectures, group discussions, investment simulations, and evaluation by pre-test and post-test instruments. The results revealed a significant improvement in students' financial literacy levels. The average pre-test score of 27.4 increased to 39.7 in the post-test, reflecting a 45% enhancement in understanding. The most significant improvements were observed in students' ability to allocate expenditures to basic needs, savings, and social activities, followed by increased awareness of the characteristics and risks of a range of investment vehicles, including equities, mutual funds, and bonds. This program demonstrates that integrating financial literacy into secondary education is effective in fostering financial awareness and developing essential money management skills from an early age.